2014
DOI: 10.1080/09593330.2014.983990
|View full text |Cite
|
Sign up to set email alerts
|

Improving legume nodulation and Cu rhizostabilization using a genetically modified rhizobia

Abstract: The rhizobia-legume interaction has been proposed as an interesting and appropriate tool for rhizostabilization of soils contaminated with heavy metals. One of the main requirements to use this symbiosis is the availability of tolerant and symbiotically effective rhizobia. The aim of this work was to improve the symbiotic properties of the arsenic-resistant wild-type strain Ensifer medicae MA11 in Cu-contaminated substrates. The copAB genes from a Cu-resistant Pseudomonas fluorescens strain were expressed in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Moreover, such a strain has already been successfully applied for phytoremediation of rice fields, in that 9% of Cd was removed from the soil within 2 months of cultivation (Ike et al, 2007). In addition to transgenic strains resistant to Cd, a genetically modified Ensifer medicae strain MA11 expressing copper tolerance genes copAB was obtained (Delgadillo et al, 2015). More recently, a double genetically modified symbiotic system was created for the phytostabilization of copper in the roots of the legume plant M. truncatula.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such a strain has already been successfully applied for phytoremediation of rice fields, in that 9% of Cd was removed from the soil within 2 months of cultivation (Ike et al, 2007). In addition to transgenic strains resistant to Cd, a genetically modified Ensifer medicae strain MA11 expressing copper tolerance genes copAB was obtained (Delgadillo et al, 2015). More recently, a double genetically modified symbiotic system was created for the phytostabilization of copper in the roots of the legume plant M. truncatula.…”
Section: Introductionmentioning
confidence: 99%
“…The blue colour indicated that the nodules were elicited by the modified microsymbiont. Moreover, since the genes copAB were located in a distal position respect to the promoter, the expression of lacZ was indicative of the correct expression of copAB, situated in a proximal position respect to the promoter (Delgadillo et al 2015). 8.53 ± 4.86* 5.55 ± 3.14* 6.11 ± 3.70* For each metal concentration, significant differences with regard to the control at p < 0.05 are indicated by *…”
Section: Effect On Nodulationmentioning
confidence: 99%
“…Plants transformed with the empty vector were used as control. The genetically modified rhizobial strain E. medicae MA11 expressing the P. fluorescens copAB genes was previously reported (Delgadillo et al 2015).…”
Section: Generation Of Genetically Modified Symbiontsmentioning
confidence: 99%
See 1 more Smart Citation
“…PGP rhizobia may play a beneficial role in protecting plants from arsenic contamination. This can be accomplished by stimulating the antioxidant enzymatic activities in plants, and stabilizing heavy metals and metalloids thereby reducing their accumulation in aerial organs [146][147][148]. For this reason, the use of PGP rhizobia in heavy metal and metalloid contaminated soils should not only promote the growth of the plant but should also immobilize and decrease the concentration of these elements in plant organs to reduce human exposure to toxic concentrations [149,150] The presence of heavy metals can also influence the results of inoculant treatment of crops.…”
Section: Plant Growth Promoting Rhizobia In Heavy Metal Contaminated mentioning
confidence: 99%